Welfare policy in the presence of unionised labour and internationally mobile firms - Silvia Rocha-Akis; Ronnie Schöb (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2009)
In oligopolistic industries that are unionised and may be affected by offshoring, falling offshoring costs have a moderating effect on trade unions. They will accept lower sector wages in order to discourage mobile forms from leaving the country. Since such wages are independent of the workers' domestic outside opportunities, wage moderation - induced by deeper economic integration - creates leeway for the government to engage in redistributive policies even if this improves the workers' domestic outside options. Only if the latter become sufficiently attractive will redistribution induce some offshoring, and it is only at that level that further economic integration will lead to both wage moderation and offshoring activities. Therefore, our analysis suggests that rather than provoking a downsizing of the welfare state, offshoring defines an upper limit for the generosity of the welfare state below which redistribution becomes less instead of more distortive.
Keywords: F16; H30; H50; J30; J50; L10; 330; offshoring; import competition; wage bargaining; oligopoly; redistribution; Einkommensumverteilung; Sozialstaat; Gewerkschaftlicher Organisationsgrad; Lohnverhandlungstheorie; Offshoring; Multinationales Unternehmen; Oligopol; Internationaler Wettbewerb; Theorie; Welt